MAKNA SUKSES DALAM QS. AL-MU’MINŪN [23]: 1–11 PERSPEKTIF TAFSIR AL-RAZI: THE CONCEPT OF SUCCESS IN QS AL-MU’MINŪN [23]: 1–11 FROM THE PERSPECTIVE OF AL-RAZI’S TAFSIR - Setyawati, Dewi Anjar; Ulfiyatin, Anis; Lestari, Fuji (Islamic Texts: Journal of Tafsir and Hadith Studies, 2025)
This study is motivated by the importance of the concept of success in the perspective of the Qur’an, particularly in QS. al-Mu’minūn [23]: 1–11, which presents the characteristics of believers who attain true prosperity. The purpose of this research is to examine the concept of success in these verses through the perspective of Tafsīr Mafātīḥ al-Ghayb by Fakhr al-Dīn al-Rāzī. The research employs a library research method with the ‘Ulūm al-Qur’an (Qur’anic exegesis approach). The primary sources consist of the Qur’an and Tafsīr Mafātīḥ al-Ghayb, while the secondary data are drawn from other tafsir works such as Tafsir al-Azhar by Hamka, Tafsir al-Muyassar by ‘Aidh al-Qarni, and Fī Ẓilāl al-Qur’an by Sayyid Quthb. The data were analyzed using a descriptive-analytical method, namely by presenting the texts of tafsir, examining the meanings contained within them, and analyzing their relevance to the focus of the study. The findings reveal that the concept of success in QS. al-Mu’minūn [23]: 1–11, according to Tafsīr Mafātīḥ al-Ghayb, is defined as the attainment of paradise by possessing seven essential traits: having faith, performing prayer with humility, avoiding futile actions, paying zakat, guarding chastity from adultery, fulfilling trusts and promises, and maintaining consistency in performing the five daily prayers. Thus, success from the Qur’anic perspective is not merely oriented toward worldly achievements but emphasizes the perfection of faith and deeds that ultimately lead to eternal happiness in the hereafter.